Synthesis, Molecular Modelling, FT-IR, Raman and NMR Characterization, Molecular Docking and ADMET Study of New Nickel(II) Complex with an N4-Tetradentate Thiosemicarbazone - Eğlence-Bakır, Songül; Çelik, Sefa; Şahin, Musa; Ozel, Ayşen E.; AKYÜZ, SEVİM; Ülküseven, Bahri (Taylor and Francis Ltd., 2021)
A new nickel(II) complex was synthesized by using S-propyl-thiosemicarbazide and 2-amino-3,5-dibromobenzaldehyde. The complex, obtained by the template effect of nickel ions, was structurally analysed by experimental and theoretical vibrational spectroscopy, NMR and density functional theory (DFT) calculations. By using DFT/B3LYP method with 6-311++G(d, p) basis set, the most stable molecular structure of the title molecule was calculated. The fundamental vibrational wavenumbers, IR and Raman intensities for the optimized structure of the molecule under investigation were determined and compared with the experimental vibrational spectra. The vibrational assignment was achieved using the calculated potential energy distributions of the vibrational modes. Moreover, the molecular electrostatic potential (MEP), the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) energies were calculated, Molecular docking of the molecule was carried out against DNA in order to identify the potential inhibitory action of the title compound. The findings suggested that the aforementioned compound has a strong binding affinity to interact with DNA residues DT8, DC9, DG12, DG16, DA17, and DA18 through the intermolecular hydrogen bonds. Also the performed in silico ADMET analysis was the prediction of the synthesized molecule’s pharmacokinetic and toxicity profile expressing good oral drug like actions and non-toxic nature. The complex has been shown to have the possibility to become a model molecule for drug development processes. Communicated by Ramaswamy H. Sarma. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ADMET; DFT Calculations; Molecular Docking; Thiosemicarbarbazone; Nickel(II) Complex